2019
DOI: 10.7554/elife.50974
|View full text |Cite
|
Sign up to set email alerts
|

Multiple kinesins induce tension for smooth cargo transport

Abstract: How cargoes move within a crowded cell—over long distances and at speeds nearly the same as when moving on unimpeded pathway—has long been mysterious. Through an in vitro force-gliding assay, which involves measuring nanometer displacement and piconewtons of force, we show that multiple mammalian kinesin-1 (from 2 to 8) communicate in a team by inducing tension (up to 4 pN) on the cargo. Kinesins adopt two distinct states, with one-third slowing down the microtubule and two-thirds speeding it up. Resisting kin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 51 publications
3
23
0
Order By: Relevance
“…We remark that an asymmetric tug-of-war may even occur in motor interactions of a single type, as recently observed in force-gliding assay experiments of kinesins moving microtubule cargoes in Tjioe et al. ( 2019 ). The analysis proposed here could be applied to models accounting for switching between different behaviors (states) of kinesin motors, such as “driving” kinesins pulling on a microtubule and “resisting” kinesins holding it back (Tjioe et al.…”
Section: Application To Cooperative and Tug-of-war Models Of Cargo Trsupporting
confidence: 77%
See 3 more Smart Citations
“…We remark that an asymmetric tug-of-war may even occur in motor interactions of a single type, as recently observed in force-gliding assay experiments of kinesins moving microtubule cargoes in Tjioe et al. ( 2019 ). The analysis proposed here could be applied to models accounting for switching between different behaviors (states) of kinesin motors, such as “driving” kinesins pulling on a microtubule and “resisting” kinesins holding it back (Tjioe et al.…”
Section: Application To Cooperative and Tug-of-war Models Of Cargo Trsupporting
confidence: 77%
“…The run lengths in panels b and d are plotted on a log-log scale to allow for visualization of differences between the models considered. The definitions of effective velocity and run length used are provided in the text of a single type, as recently observed in force-gliding assay experiments of kinesins moving microtubule cargoes in Tjioe et al (2019). The analysis proposed here could be applied to models accounting for switching between different behaviors (states) of kinesin motors, such as "driving" kinesins pulling on a microtubule and "resisting" kinesins holding it back (Tjioe et al 2019).…”
Section: Tug-of-war Models Of Cargo Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…We confirmed that tau was also inhibitory to both motors without added salt ( Figure S3B-E, Movie S2), and both K560 and DDR quickly detached when they encountered a tau condensate on the MT (Siahaan et al, 2019)( Figure S3F). We also tested whether multiple motor assemblies walk more successfully on taucoated MTs, as this was shown to be an effective strategy to bypass static obstacles on MTs (Ferro et al, 2019;Tjioe et al, 2019). MT decoration by tau fully inhibited the motility of beads driven by multiple K560 or DDR motors as strongly as it inhibited individual motors ( Figure S4).…”
Section: The Regulatory Role Of a Map Cannot Be Predicted Based On Mtmentioning
confidence: 99%